Preparation and storage method and application of near-infrared super carbon nanodots
Through electrostatic and hydrogen bonding, the carbon nanodots are self-assembled, and supercarbon nanodots with a light absorption range expanded to near infrared are prepared, which solves the problem of the narrow absorption range of existing carbon nanodots and expands its application prospects in many fields.
Patent Information
- Application Number
- CN202411969532.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-21
AI Technical Summary
The existing carbon nanodots have a narrow absorption range, mainly concentrated in ultraviolet, blue or green light areas, making it difficult to effectively absorb light in red and near-infrared areas, limiting its application in deep tissue therapy and other fields.
Supercarbon nanodots are self-assembled through electrostatic and hydrogen bonding to prepare supercarbon nanodots. The specific method includes placing the carbon nanodots in an aqueous system and allowing them to stand for the first assembly, and then performing secondary assembly under low temperature and dry conditions to expand their absorbance range to the near infrared region.
The absorbance range of supercarbon nanodots is close to the near-infrared region, widening the absorbance band, significantly expanding its application prospects in the fields of medical, energy and environment, and improving the purity and stability of the product.
Smart Images

Figure CN119662245A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of carbon nanomaterials, and in particular to a preparation and storage method and application of near-infrared super carbon nanodots. Background Art
[0002] Carbon nanodots belong to the category of new carbon-based nanomaterials, and their remarkable features are extremely small size, excellent water solubility, excellent optical properties, low toxicity level and excellent biocompatibility. Based on these characteristics, carbon nanodots have been widely used in the biomedical field.
[0003] However, the main light absorption bands of carbon nanodots are mostly in the ultraviolet, blue or green light spectrum range. This characteristic significantly restricts their application in the long wavelength region, which means that carbon nanodots can only act on the surface or shallow parts of biological tissues in biomedical applications, and it is difficult to penetrate into deep tissues to exert therapeutic effects. Although surface passivation, heteroatom doping and size control are commonly used to modulate the absorption bands of carbon nanodots, these conventional methods cannot enable carbon nanodots to achieve effective light absorption in the red and near-infrared (NIR) regions, which greatly limits their further expansion and application in related fields such as deep tissue treatment.
[0004] Therefore, in-depth research on the synthesis methods and assembly strategies of carbon nanodots is of great scientific value. Through fine-tuning of the synthesis process and ingenious design of the assembly method, it is expected that the various properties of carbon nanodots can be precisely adjusted to break through the limitations of the existing light absorption range and achieve effective expansion from the ultraviolet, blue, and green light regions to the red and near-infrared regions. It can also open up broader application prospects for carbon nanodots in many fields, such as deep tissue imaging and treatment in biomedicine, efficient photoelectric conversion in the energy field, and deep photocatalysis in the environmental field. Summary of the invention
[0005] In view of this, the purpose of this application is to provide a method for preparing and storing near-infrared super carbon nanodots and their application, so as to solve the problem that the existing carbon nanodots have a narrow absorption range and a limited application range.
[0006] In order to achieve the above technical purpose, the present application provides a super carbon nanodot, which is self-assembled by carbon nanodots through electrostatic action and hydrogen bonding action in sequence.
[0007] Furthermore, the specific preparation method is as follows:
[0008] Primary assembly: placing the carbon nanodots in a water-containing system and letting them stand for a preset period of time to obtain primary assembled carbon nanodots; secondary assembly: taking the primary assembled carbon nanodots and placing them in a sealed state at low temperature and dry conditions and letting them stand for a preset period of time to obtain super carbon nanodots.
[0009] Furthermore, the preparation method of carbon nanodots is as follows: a mixed solution containing a carbon source and a nitrogen source is heated to perform a hydrothermal synthesis reaction to obtain carbon nanodots.
[0010] Furthermore, the carbon source is one of citric acid, ethylenediaminetetraacetic acid, glycerol, glucose, fructose, sucrose, chitosan, and starch; and the nitrogen source is one of urea and ammonia water.
[0011] Furthermore, in the mixed solution, the mass concentration of citric acid is 120 g / L, and the mass concentration of urea is 240 g / L.
[0012] Furthermore, the preset static time is 0 to 14 h.
[0013] Furthermore, the preset static time is 8 hours; the preset static period is 24 hours.
[0014] Furthermore, the super carbon nanodots were stored at 8 °C.
[0015] Furthermore, the super carbon nanodots are stored in a dry form.
[0016] The present application provides an application of super carbon nanodots, which is applied in the field of fluorescence quenching.
[0017] In summary, the present application provides a method for preparing super carbon nanodots, in which the carbon nanodot solution is allowed to stand for a preset time for preliminary assembly, and then secondary assembly is performed under low temperature, dry and sealed conditions. The super carbon nanodots prepared by this method show significant advantages, and their absorption range is close to the near-infrared region, which greatly broadens the absorption band and demonstrates potential application value in the medical field. Compared with the prior art, the preparation method provided by the present application can be successfully prepared in a water-free dry environment, abandoning the dependence on aqueous media in traditional methods, and effectively avoiding various complex problems that may be caused by the presence of aqueous media, such as impurity introduction, agglomeration, etc., thereby ensuring the purity and uniformity of the product. From the perspective of storage characteristics, the super carbon nanodots prepared in the present application have the ability to be stored for a long time in an aqueous solution or dry form under low temperature conditions; among them, when stored in a dry form, it can more effectively maintain its structural stability and performance integrity, and extend its effective storage period. In addition, super carbon nanodots also show broad application prospects in the field of fluorescence technology. With their unique optical properties, they are expected to provide a new material basis and technical support for the further development of fluorescence technology, and promote the innovative application of related technologies in multiple sub-fields such as bioimaging, optical sensing, and optoelectronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0019] Figure 1 UV-Vis spectrum test chart of super carbon nanodots at different initial assembly times provided in Example 1 of the present application;
[0020] Figure 2 FT-IR spectra of super carbon nanodots at 0 and 8 h of initial assembly provided in Example 1 of the present application;
[0021] Figure 3 This is a TEM image of the super carbon nanodots after 8 h of initial assembly provided in Example 1 of the present application;
[0022] Figures 4 to 6 They are respectively the UV-Vis spectra of the super carbon nanodots with the same storage concentration at different storage times provided in Examples 2 to 4;
[0023] Figure 7-8 UV-Vis spectra and solution color comparison diagrams of super carbon nanodots at different storage concentrations under the same storage time provided in Examples 2 to 4;
[0024] Fig. 9 The UV-Vis spectrum of the super carbon nano solution with a mass concentration of 0.5 mg / mL at a storage temperature of 30°C provided in Example 5;
[0025] Figures 10-11 UV-Vis spectra and solution color comparison diagrams of the super carbon nano-solution with a mass concentration of 0.5 mg / mL at different storage temperatures provided in Example 2 and Example 5;
[0026] Fig.12 UV-Vis spectra of the super carbon nanodot materials provided in Examples 4 and 6 of the present application under different storage conditions;
[0027] Fig.13 The upconversion fluorescence spectra of UCNP@aptamer, UCNP@aptamer@super carbon nanodots and UV-Vis spectra of super carbon nanodots provided in Example 7 of the present application;
[0028] Fig.14 A physical picture of the sample provided for comparative example 1 of this application;
[0029] Fig.15UV-Vis spectrogram of the sample provided for comparative example 1 of the present application;
[0030] Fig.16 A physical picture of the sample provided for comparative example 2 of this application;
[0031] Fig.17 This is the UV-Vis spectrum of the sample provided for Comparative Example 2 of the present application. DETAILED DESCRIPTION
[0032] The technical solutions of the embodiments of the present application will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the specification of the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection requested by the present application.
[0033] The sources of all raw materials in the present invention are not particularly limited and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.
[0034] The embodiment of the present invention provides a super carbon nanodot, which is self-assembled by carbon nanodots through electrostatic action and hydrogen bonding action.
[0035] In some embodiments, super carbon nanodots are prepared in the following manner: primary assembly: placing the carbon nanodots in an aqueous system and letting them stand for a preset period of time to obtain primary assembled carbon nanodots; secondary assembly: taking the primary assembled carbon nanodots and placing them in a sealed state under low temperature and dry conditions and letting them stand for a preset period of time to obtain super carbon nanodots.
[0036] In some embodiments, the method for preparing carbon nanodots is as follows: a mixed solution containing a carbon source and a nitrogen source is heated to perform a hydrothermal synthesis reaction to obtain carbon nanodots.
[0037] Preferably, the preset standing time is 0-14 h. Specifically, the heating temperature is 160-200 °C.
[0038] More preferably, the preset static time is 8 hours; the preset static period is 24 hours.
[0039] Preferably, the carbon source is one of citric acid, ethylenediaminetetraacetic acid, glycerol, glucose, fructose, sucrose, chitosan, and starch; and the nitrogen source is one of urea and ammonia water.
[0040] More preferably, in the mixed solution, the mass concentration of citric acid is 120 g / L, and the mass concentration of urea is 240 g / L.
[0041] The present application provides a storage method for super carbon nanodots, wherein the super carbon nanodots are stored under low temperature conditions.
[0042] Preferably, the storage is carried out at 8°C, and the storage method is: the storage operation is carried out in a solution state with a mass concentration of 50-150 mg / L.
[0043] Preferably, the super carbon nanodots are stored in a dry powder form at 8° C. Specifically, they are stored for at least 65 days.
[0044] The applicant further provides the following reference specific embodiments to describe the present invention. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.
[0045] Example 1
[0046] The present invention provides a method for synthesizing super carbon dots, comprising the following steps:
[0047] Step S1, solution preparation: weigh citric acid and urea, and mix the two with water to form a mixed solution with a citric acid mass concentration of 120 g / L and a urea concentration of 240 g / L;
[0048] Step S2, hydrothermal reaction: placing the mixed solution in a hydrothermal synthesis reactor, heating the temperature to 160° C., and performing the hydrothermal reaction for 4 h to obtain carbon nanodots;
[0049] Step S3, initial assembly: after the hydrothermal reaction is completed, the hydrothermal reactor is opened and allowed to stand for initial assembly of the mixed system after the reaction, and the standing time is 0, 2, 4, 6, 8, 10, 12, and 14 h respectively;
[0050] Step S4, post-treatment operation: after standing, anhydrous ethanol is added to the mixed system, and then placed in a centrifuge for centrifugation at a speed of 9600 r / min for 10 min. After the centrifugation, the solid matter is freeze-dried at -50°C for 6 h to obtain the primary assembled carbon nanodots;
[0051] Step S5, secondary assembly: the primary assembled carbon nanodots were transferred to an agate mortar and ground for 5 min to obtain primary assembled carbon nanodot powder, and the primary assembled carbon nanodot powder was sealed and stored at 8°C for 24 h to complete secondary assembly and obtain super carbon nanodots.
[0052] Test 1: UV-Vis spectrum test:
[0053] The super carbon nanodots prepared in Example 1 were prepared into a super carbon nanodot solution with a concentration of 0.5 mg / mL, and UV-Vis spectrum test was performed on it. The test results are shown in FIG. Figure 1 shown.
[0054] As shown in Figure 1 (a), the super carbon nanodots have strong absorption bands with central wavelengths at 345 nm and 690 nm, of which 690 nm is a broad near-infrared absorption peak. This feature indicates that the carbon nanodots have been successfully assembled into super carbon nanodots. Figure 1 (b) It can be seen that in the static interval of 0 to 8 hours, the absorption peak of super carbon nanodots at 690 nm showed a gradually increasing trend, which indicates that the assembly degree of super carbon nanodots during this period increased steadily with the passage of time, especially when the initial assembly time reached 8 hours, the absorption intensity of super carbon nanodots at 690 nm climbed to the highest value, thus the optimal initial assembly time for super carbon nanodot synthesis was selected as 8 hours. Figure 1 (c) It can be seen that as the initial assembly time is further extended to 8-14 h, the absorption intensity of the super carbon nanodots at 690 nm begins to gradually weaken, and the peak intensity at 345 nm remains stable, unaffected by the change in the initial assembly time. This phenomenon fully demonstrates that during this period, the assembly degree of the super carbon nanodots decreases with the increase of assembly time. Figure 1 (d) shows a direct comparison of super carbon nanodot aqueous solutions (concentration 0.5 mg / mL) with initial assembly times of 2, 4, 8, and 14 h. It can be clearly observed from the figure that the color of the aqueous solution changes from yellow-green to light blue, blue, and light blue in sequence with the extension of the initial assembly time. This gradual change process indicates that the assembly degree of super carbon nanodots continues to rise and reaches a peak at 8 hours, and then gradually decreases. This phenomenon is perfectly consistent with the results presented by the absorption spectrum.
[0055] Test 2: Fourier Transform Infrared Spectroscopy (FT-IR)
[0056] The carbon nanodots with an assembly time of 0 h and the super carbon nanodots with an assembly time of 8 h in step S3 were pressed into a tablet with potassium bromide and then subjected to FT-IR testing. The test results are as follows: Figure 2 As shown. Figure 2 It can be seen that infrared spectrum has , , Three characteristic absorption bands, indicating the presence of amino, carboxyl and pyridine nitrogen groups in carbon nanodots. The positively charged amino group and the negatively charged carboxyl / pyridine nitrogen groups are located at different positions on the surface of carbon nanodots. Based on the possibility that the amino group is on one side and the carboxyl / pyridine nitrogen is on the other side of the surface of a single carbon nanodot, adjacent carbon nanodots can be assembled to form super carbon nanodots through electrostatic interactions and hydrogen bonding between particles. By comparing the spectra of carbon nanodots and super carbon nanodots, it is found that the characteristic absorption peaks of C=N, C=O and amino groups in super carbon nanodots have shifted to the low wave number direction compared with carbon nanodots. This displacement of absorption peaks strongly confirms that hydrogen bonds were successfully constructed between particles during the initial assembly of super carbon nanodots. The reason is that the formation of hydrogen bonds will change the electron cloud distribution and vibration environment of the relevant chemical bonds, thereby causing regular changes in the position of their characteristic absorption peaks in the infrared spectrum. This change provides an important spectroscopic basis for the assembly mechanism and structural characteristics of super carbon nanodots.
[0057] Test 3: Transmission electron microscopy (TEM) test
[0058] The super carbon nanodots with an initial assembly time of 8 hours were tested by TEM. The test results are as follows: Figure 3 As shown in the figure, the size of the elliptical carbon nanodots is about 50 nm; due to the randomness of the assembly, the super carbon nanodots formed by the stacking of carbon nanodots are irregular in shape and size, and the size is about 100 nm~600 nm, which further verifies the assembly process and characteristics of super carbon nanodots from the microscopic structure level, and provides intuitive and reliable microscopic evidence for the existence morphology and formation mechanism of super carbon nanodots.
[0059] Example 2
[0060] The present application provides a storage method of super carbon dots, comprising the following steps:
[0061] Step S1, solution preparation: weigh citric acid and urea, and mix the two with water to form a mixed solution with a citric acid mass concentration of 120 g / L and a urea concentration of 240 g / L;
[0062] Step S2, hydrothermal reaction: placing the mixed solution in a hydrothermal synthesis reactor, heating the temperature to 160° C., and performing the hydrothermal reaction for 4 h to obtain carbon nanodots;
[0063] Step S3, initial assembly: after the hydrothermal reaction is completed, the hydrothermal reactor is opened and allowed to stand for 8 h, and the mixed system after the reaction is initially assembled;
[0064] Step S4, post-treatment operation: after standing, anhydrous ethanol is added to the mixed system, and then placed in a centrifuge for centrifugation at a speed of 9600 r / min for 10 min. After the centrifugation, the solid matter is freeze-dried at -50°C for 6 h to obtain the primary assembled carbon nanodots;
[0065] Step S5, secondary assembly: the primary assembled carbon nanodots were transferred to an agate mortar and ground for 5 min to obtain primary assembled carbon nanodot powder, and then the primary assembled carbon nanodot powder was sealed and stored at 8°C for 24 h to complete secondary assembly and obtain super carbon nanodots;
[0066] Step S6: The obtained super carbon nanodots were configured into a 0.5 mg / mL super carbon nanodot solution, and the solution was stored at 8°C for 0 h, 6 h, 12 h, 24 h, 36 h, 48 h, 60 h, 72 h, 84 h, 4 d, 5 d, 6 d, 7 d, and 8 d, respectively.
[0067] Embodiment 3-4
[0068] The present application provides a storage method for super carbon dots, which is different from Example 2 in that the mass concentrations of the super carbon nanodot solutions are 50 mg / mL and 150 mg / mL, respectively.
[0069] Test 1: UV-Vis spectroscopy test
[0070] Figures 4 to 6 The UV-Vis spectra of super carbon nanodots with the same storage concentration at different storage times provided in Examples 2 to 4 are shown in Figure 1. As can be seen from the figure, with the increase of storage time, the intensity of the absorption peak of the super carbon nanomaterial at 690 nm gradually decreases, which indicates that the super carbon nanomaterial has a certain instability.
[0071] Figure 7-8 The UV-Vis spectra and solution color comparison diagrams of super carbon nanodots at different storage concentrations under the same storage time provided in Examples 2 to 4. As can be seen from the figure, as the storage concentration of super carbon nanodots gradually increases, the rate of decrease of the absorption peak intensity at 690nm gradually slows down. This phenomenon shows that compared with low-concentration super carbon nanosolutions, high-concentration super carbon nanosolutions show more excellent stability.
[0072] Example 5
[0073] The present application provides a storage method for super carbon dots, which is different from Example 2 in that, in step S6, the storage temperature is 30°C.
[0074] Test 1: UV-Vis spectroscopy test
[0075] Fig. 9 The UV-Vis spectrum of the super carbon nano solution with a mass concentration of 0.5 mg / mL provided in Example 5 at a storage temperature of 30°C. Fig. 9 It can be seen that compared with Example 2 stored at 8°C, the absorption peak intensity at 690 nm of Example 5 stored at 30°C is significantly lower. This phenomenon clearly shows that with the gradual increase in storage temperature, the absorption peak intensity of the super carbon nanomaterial at 690 nm shows a trend of gradually decreasing. It can be inferred that the super carbon nanomaterial has a certain degree of instability under non-low temperature conditions. The increase in temperature is very likely to cause subtle changes in the internal structure of the super carbon nanomaterial or the chemical bonds on its surface, thereby affecting the material's absorption characteristics for light of a specific wavelength, causing the absorption peak intensity at 690 nm to decrease.
[0076] Figures 10-11 UV-Vis spectra and solution color comparison diagrams of super carbon nanodot solutions with a mass concentration of 0.5 mg / mL at different storage temperatures provided for Example 2 and Example 5. As can be seen from the figure, when the storage temperature of super carbon nanodots gradually decreases, the intensity decrease rate of its absorption peak at 690 nm shows a slowing trend. This phenomenon strongly indicates that compared with the storage environment at room temperature or high temperature, the super carbon dot samples stored in a low temperature environment show more superior stability.
[0077] Example 6
[0078] The present application provides a storage method for super carbon dots, which is different from Example 4 in that, in step S6, the super carbon nanodots are stored in a dry powder form at a low temperature of 8° C. for 65 days.
[0079] Test 1: UV-Vis spectroscopy test
[0080] In order to more intuitively observe the stability of super carbon nanodots in different storage forms, the super carbon nanodot solution stored at 8°C for 0 and 8 h in Example 4 was integrated and compared with the stability of the super carbon nanodot dry powder provided in this example. The results are as follows: Fig.12As shown in the figure. It can be seen from the figure that under the specific conditions of low temperature (8°C), for the high concentration aqueous solution (150mg / mL) of super carbon nanodot materials, the sample stored for 0 h showed the strongest absorption peak at 690 nm, while the sample stored for 8 days had a significant decrease in the absorption peak intensity at 690 nm. On the other hand, although the absorption peak intensity of the sample stored in a solid aggregate state for 65 days at 690 nm also decreased to a certain extent, the decrease was relatively small compared with the sample stored in an aqueous solution for 8 days. Based on the above results, it can be clearly concluded that the storage form of solid aggregate state has a positive promoting effect on the stability of super carbon nanodot materials. This may be because in the solid aggregate state, the interaction between super carbon nanodots is more stable, reducing the interference of external factors on its structure and performance, so that its optical properties can be better maintained during long-term storage, especially the absorption peak intensity at 690 nm, which provides an important reference for the storage and performance maintenance of super carbon nanodot materials in practical applications.
[0081] Example 7
[0082] The present application provides a fluorescence sensor, and the specific preparation steps are as follows:
[0083] The super carbon nanodots prepared in Example 2 were prepared into a super carbon nano solution with a concentration of 0.1 mg / mL, and mixed with aptamer-modified NaYbF4:0.2Gd / 0.18Y / 0.02Er@NaYF4 upconversion luminescent nanoparticles (UCNPs@aptamer, 0.1 mg / mL), and the π-π interaction between the super carbon nanodots and the aptamer chain was used to form a UCNPs@aptamer@super carbon nanodot complex.
[0084] Detection: Test the upconversion fluorescence properties of UCNPs@aptamer, UCNPs@aptamer@super carbon nanodots and the UV-Vis spectrum of super carbon nanodots.
[0085] Fig.13The upconversion fluorescence spectra of UCNP@aptamer, UCNP@aptamer@super carbon nanodots and UV-Vis spectra of super carbon nanodots provided in Example 7 of the present application are compared. As can be seen from the figure, under the condition of 980 nm laser excitation, UCNP@aptamer exhibits upconversion fluorescence emission at 545 nm and 660 nm. The super carbon nanodot material presents a wide and strong absorption peak at 690 nm, which completely overlaps with the upconversion fluorescence emission peak of UCNP@aptamer at 660 nm. Further observation revealed that UCNP@aptamer@super carbon nanodots also have upconversion fluorescence emission at 545 nm and 660 nm, however, compared to when UCNP@aptamer exists alone, its upconversion fluorescence intensity at 660 nm is significantly reduced. Based on the above phenomena, it can be clearly concluded that super carbon nanodots have an extremely excellent fluorescence quenching effect at 690 nm in the near-infrared. This characteristic makes super carbon nanodots have great potential to become near-infrared quenchers when constructing related fluorescence sensors. The reason is that when super carbon nanodots interact with UCNP@aptamer, due to the overlap of its strong absorption at 690 nm and the fluorescence emission of UCNP@aptamer at 660 nm, energy transfer occurs between super carbon nanodots and UCNP@aptamer, resulting in a decrease in the fluorescence intensity of UCNP@aptamer@super carbon nanodots at 660 nm, showing a strong fluorescence quenching ability, which provides a key material basis for the development of high-performance fluorescence sensors.
[0086] Comparative Example 1
[0087] The comparative example of this application refers to CN105271174B, and provides a method for synthesizing super carbon nanodots, comprising the following steps:
[0088] Step S1, solution preparation: weigh citric acid and urea, and mix the two with water to form a mixed solution with a citric acid mass concentration of 120 g / L and a urea concentration of 240 g / L;
[0089] Step S2, hydrothermal reaction: placing the mixed solution in a hydrothermal synthesis reactor, heating the temperature to 160° C., and the hydrothermal reaction time is 4 h;
[0090] Step S3, initial assembly: after the hydrothermal reaction is completed, open the hydrothermal reactor and let it stand for 0 h;
[0091] Step S4, post-treatment operation: after standing, add anhydrous ethanol to the mixed system, then centrifuge at 9600 r / min for 10 min, and freeze-dry the solid matter at -50°C for 6 h to obtain carbon nanodots;
[0092] Step S5, secondary assembly: the carbon nanodots were transferred to an agate mortar and ground for 5 min to obtain yellow-green carbon nanodot powder, which was then placed in a room temperature environment with a relative humidity of 60% for 14 days to obtain a sample.
[0093] Test 1: UV-Vis absorption test
[0094] Fig.14 The color comparison chart of the sample synthesized in the comparative example of this application after being placed for 0 hours and then placed in a room temperature environment with a relative humidity of 60% for 14 days. Fig.14 It can be clearly found that after the sample was placed in an environment with a relative humidity of 60% for 14 days, its appearance changed significantly, from the original yellow-green powder to yellow powder, instead of obtaining blue-black super carbon nanodots as described in patent CN105271174B. It can be inferred that the condition of room temperature storage has an impact on the assembly process of the super carbon nanodots in this comparative example, which leads to the final appearance not meeting expectations. Fig.15 The UV-visible absorption spectrum of the sample synthesized in the comparative example of this application was placed in a room temperature environment with a relative humidity of 60% for 14 days. A careful analysis of the figure shows that after being placed in a room temperature environment with a relative humidity of 60% for 14 days, the absorption peak at 670 nm basically disappears. This phenomenon means that the assembly of super carbon nanodots has not been successfully achieved, because the change in the absorption peak intensity is often closely related to the structure and assembly state of the material. The sharp drop in the absorption peak intensity here indicates that its internal structure and assembly degree have not reached the ideal state. It can be clearly concluded from the various results of this comparative example that according to the carbon nanodot assembly method described in patent CN105271174B, the target super carbon nanodots cannot be successfully obtained, and the experimental conditions described in the patent are complex, costly, and difficult to achieve. Therefore, it is necessary to explore a simple, economical, and feasible method for synthesizing super carbon dots.
[0095] Comparative Example 2
[0096] The difference from Comparative Example 1 is that in step S3, after the hydrothermal reaction is completed, the reaction solution is left to stand for 2 h; and in step S5, the temperature during the secondary assembly is 8°C.
[0097] Fig.16 The color comparison chart of the sample synthesized for the comparative example of this application after being placed in a low temperature environment (8°C) with a relative humidity of 60% for 14 days. Fig.16It can be clearly seen that after the sample was placed in a low temperature environment with a relative humidity of 60% for 14 days, its color changed significantly from the original blue-green powder to a blue-black powder. It is particularly important to point out that the storage temperature in this comparative example is set to 8°C. Based on this phenomenon, it is preliminarily inferred that under this temperature condition, the assembly of carbon nanodots is in the forward direction.
[0098] Fig.17 The UV-visible absorption spectra of the samples synthesized in the comparative examples of the present application which were placed in a low temperature environment (8°C) with a relative humidity of 60% for 14 days were compared. Fig.17 It can be seen that after being placed in an environment of 8 ° C and a relative humidity of 60% for 14 days, the absorption peak intensity of 670 nm is high, indicating that the assembly of super carbon nanodots is successful. This comparative example shows that low temperature conditions play a key role in the assembly process of carbon nanodots, and it is one of the important conditions to ensure that carbon nanodots can be assembled smoothly. In addition, by allowing the aqueous solution to stand for a certain period of time after the hydrothermal reaction, the preliminary assembly of super carbon nanodots can be completed. This mode of operation can effectively shorten the time for subsequent freeze-drying for secondary assembly to a large extent and improve the efficiency of the entire synthesis process. The super carbon dot assembly temperature described in patent CN105271174B is fuzzy, the assembly time is too long, and the experimental conditions described in the patent are complex, costly, and difficult to achieve. In addition, the reaction solution in the comparative example of this application has a standing time of 2 h, and the absorption peak intensity of 670 nm does not show the maximum intensity, which means that there is still room for further optimization.
[0099] The above are only preferred embodiments of the present application and are not intended to limit the present invention. Although the present application has been described in detail with reference to the examples, those skilled in the art can still modify the technical solutions recorded in the aforementioned examples or make equivalent substitutions for some of the technical features therein. However, any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A super carbon nanodot, characterized in that: It is self-assembled by carbon nanodots through electrostatic interaction and hydrogen bonding.
2. The super carbon nanodot according to claim 1, characterized in that: The specific preparation method is as follows: Initial assembly: placing the carbon nanodots in a water-containing system and leaving them to stand for a preset time to obtain initially assembled carbon nanodots; Secondary assembly: The carbon nanodots assembled initially are placed in a sealed state at low temperature and in a dry environment for a preset period of time to obtain super carbon nanodots.
3. The super carbon nanodot according to claim 1, characterized in that: The preparation method of the carbon nanodots is as follows: A mixed solution containing a carbon source and a nitrogen source is heated to perform a hydrothermal synthesis reaction to obtain carbon nanodots.
4. The super carbon nanodot according to claim 3, characterized in that: The carbon source is one of citric acid, ethylenediaminetetraacetic acid, glycerol, glucose, fructose, sucrose, chitosan, and starch; and the nitrogen source is one of urea and ammonia water.
5. The super carbon nanodot according to claim 3, characterized in that: In the mixed solution, the mass concentration of citric acid is 120 g / L, and the mass concentration of urea is 240 g / L.
6. The super carbon nanodot according to claim 2, characterized in that: The preset static time is 0 to 14 hours.
7. The super carbon nanodot according to claim 6, characterized in that: The preset static time is 8 hours; the preset static period is 24 hours.
8. A method for storing super carbon nanodots according to any one of claims 1 to 7, characterized in that: The super carbon nanodots are stored at 8°C.
9. The method for storing super carbon nanodots according to claim 8, characterized in that: The super carbon nanodots are stored in a dry form.
10. A use of the super carbon nanodots according to any one of claims 1 to 7, characterized in that: Applied in the field of fluorescence quenching.
Citation Information
Patent Citations
Super carbon nanodots with strong near-infrared absorption, preparation method thereof and applications
CN105271174B